Highly ordered TiO2 nanotube-stumps with memristive response - Yoo, Jeong Eun; Lee, Kiyoung; Tighineanu, Alexei; Schmuki, Patrik (Electrochemistry Communications, 2013)
In the present work, we produce highly ordered and defined short aspect ratio self-organized TiO2 nanotubes – so called titania nanotube stumps [TNS] – by anodizing Ti in a HF/H3PO4 electrolyte. These TNS-layers are ideal for a conformal filling by metal sputter deposition. After decorating amorphous TNS with a Pt top contact, we investigate the solid-state current–voltage behavior and find a strongly pronounced memristic behavior. We ascribe the finding to the high vacancy density present in TNS bottoms prepared under high ion flux conditions.
EAM Import::2019-03-13